2013
DOI: 10.1155/2013/643780
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilation/Cutting: The Secret World of Women as Seen by Men

Abstract: Efforts aimed at the abandonment of Female Genital Mutilation/Cutting (FGM/C) in the communities where it is deeply rooted have extensively considered and addressed women's perceptions on the issue, leaving those of men barely acknowledged. Although the practice is generally confined to the secret world of women, it does not mean that men cannot be influential. Indeed, men can play an important role in prevention. In order to address this gap, and having as background an extensive ethnographic field work, a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 13 publications
7
47
0
Order By: Relevance
“…Those who believed that there is no religious prescription firmly rejected the practice, while those who believed in the hadiths indicating that Muhammad recommended making a small cut on the external genitals of the woman, firmly supported the practice. Kaplan found similar results among different Muslim ethnic groups in Gambia (Kaplan et al, 2013).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Those who believed that there is no religious prescription firmly rejected the practice, while those who believed in the hadiths indicating that Muhammad recommended making a small cut on the external genitals of the woman, firmly supported the practice. Kaplan found similar results among different Muslim ethnic groups in Gambia (Kaplan et al, 2013).…”
Section: Resultssupporting
confidence: 54%
“…On the other hand, they often referred to the hadiths to justify the acceptance of the practice by Islam (Hadiths: stories handed down orally and later recorded, related to the actions and sayings of the Prophet Muhammad, which represent, after the Qur'an, the second source of Islamic teachings) (Scolart, 2004). The perception of the practice as an Islamic requirement has been reported among men in Sudan (Almroth et al, 2001;Herieka and Dhar, 2003;Berggren et al, 2006) and Gambia (Kaplan et al, 2013). Interviews with 222 male university students in Khartoum, Sudan, found that only 14 percent supported the practice.…”
Section: Resultsmentioning
confidence: 99%
“…We Mothers and older female relatives are usually the main proponents of FGC and arrange a girl's FGC procedure, most commonly by a traditional practitioner 52,53 . In West Africa, FGC is usually performed during infancy or before age five and in the five study countries 76-94% of girls with FGC were cut before age five 42 .…”
Section: Extended Methods A) Demographic and Health Surveys (Dhs)mentioning
confidence: 99%
“…Female genital mutilation (FGM) is defined as partial or total removal of external female genitalia for nontherapeutic indications . This practice is deeply rooted in culture, with social obligation, rites of passage, marriageability, the maintenance of marital fidelity, and aesthetics considered to be the primary reasons for its continuation …”
Section: Introductionmentioning
confidence: 99%